Optic Neuritis Visual Loss after Intragastric Botulinum Toxin A Injection: A Case Report - Shushtarian, Seyed Mohammad Masoud; Jamshidi, Gholamreza; Mohammad-Rabei, Hossein; Shojaei, Ahmad; Eslami Vaghar , Mohammad (Journal of Ophthalmic and Optometric Sciences, 2025)
Intragastric botulinum toxin A is increasingly used as an endoscopic adjunct for weight reduction, and although generally safe, rare neurological and ophthalmic adverse effects have been reported. We describe the case of a 37-year-old woman who developed dimming of vision in the left eye twelve days after intragastric botulinum toxin A injection. Visual evoked potential revealed delayed P100 latency in the affected eye, while the contralateral eye was normal, and magnetic resonance imaging demonstrated inflammation of the left optic nerve. Demyelinating disease was excluded through appropriate investigations. The close temporal relationship between botulinum toxin exposure and symptom onset, along with the absence of alternative etiologies, supported a diagnosis of toxin-related optic neuritis. This case highlights that intragastric botulinum toxin A may rarely precipitate optic nerve involvement and emphasizes the importance of patient counseling and prompt ophthalmologic assessment when visual symptoms occur.